Current advancement in the application of prime editing - Huang, Zhangrao; Liu, Gang (Frontiers in Bioengineering and Biotechnology, 2023)
Prime editing (PE) is a precise genome manipulation technology based on the “search and replace” approach of the CRISPR-Cas9 system, while it does not require the exogenous donor DNA and the DNA double-strand breaks (DSBs). Comparing the base editing technology, the editing scope of prime editing has been widely expanded. Prime editing has been successfully applied in a variety of plant cells, animal cells and the model microorganism Escherichia coli so far, and it has shown a good application potential in breeding and genomic functional study of animals and plants, disease treatment, and modification of the microbial strains. In this paper, the basic strategies of prime editing are briefly described, and its research progress is summarized and prospected from the application of multiple species. In addition, a variety of optimization strategies for improving its efficiency and specificity of prime editing are outlined.